The Place of Drama in Ritual African Theatre - Figueiredo, Rosa Branca (2016)
Ritual drama staged in traditional African festivals: large open spaces big enough to accomodate actors and audiences who are sometimes in thousands. The main determinant of location, however, is not just availability of space, but a place that is ritually significant in the experience of the people. At festival time this place assumes its metaphysical reality and is a piece of sanctified ground.